Strategic management accounting : concepts, processes and issues - Hoque, Zahirul (London : Spiro, 2002)
This text supports the view that traditional management accounting systems are no longer sufficient in today's competitive environment. The book takes a comprehensive and multidisciplinary look at the design and use of accounting and performance measurement systems within a business context.
Includes bibliographical references and index.
oif 11/03/15
Loan
Keywords: Managerial accounting; Strategic planning -- Accounting